Formulating DNA Chains Using Effective Calculability - Shah, Syed Atif Ali; Khan, Zafar; Rauf, Zubia; Shah, Syed Asif Ali (International Journal of Computer (IJC), 2018)
Nearly all computational algorithms are modeled as ‘Effective Calculability’ i.e Finite State Model and Lambda Calculus. Effectively calculable function Comprise of three parts: the info, the yield, and the finite state function or transition function. It takes stream of data as input and translates to specific output, as defined by transition function [1]. The aftereffect of this conversion is another flood of information or the yield. Both i.e info and yield information streams comprise of arrangements of characters and are known as strings. DNA exhibits a property of being a pattern of strings. Automatic machines like automata and Lambda Calculus or simply the Effective Calculability [8] can be an efficient approach to study these patterns. By the introduction of Effective Calculability we can express the pattern of DNA in much better way. The transition function runs stepwise each character of the information string to produce the output string. The transformations achieved by the transition function are relatively simple in nature. Complex computations and operations can be affected by linking together several Effective Calculability switches so that the output string of one switch becomes the input string of another switch.